Growth performance of Fragaria x ananassa "Sweet Charlie" to different culture media and varying pH of hydroponic nutrient solution - Lapuz, Mayveline R.; Daquigan, Madonna C.
Hydroponics is an alternative way of cultivating crop using water containing essential nutrients fro plant growth. This study focused on comparing the effectiveness of this technique on Fragaria x ananassa at varying pH and concentration of the nutrient solution and compared with the traditional way of cultivating crops using soil from a forest and agricultural land. Results from this study showed that it is possible to grow Fragaria x ananassa in two different hydroponics nutrient solutions and it was observed that plants responded best at pH 6. The response of the plants to pH4, 6 and 8 are statistically different from each other based on the analysis of variance. Comparatively,root length was longer in the hydroponics - reared strawberries relative to plants grown in soil. The results from the hydroponics and the traditional way of crop cultivation of Fragaria x ananassa are statistically different based of the growth performance -- Author's abstract.